Aplikasi E-Ticket Berbasis Android - Roychan Faqih, Achmad; Aris Widya, Moh. Anshori (Dike, 2023)
The development of technology is growing rapidly nowadays, one of them is an mobile system that widely used to facilitate all affairs from all fields that can change people's behavior towards the digital era, so that society is greatly facilitated in all aspects, e-tickets are one of the system developments. information that is currently widely used on various platforms such as smartphones and computers, android is an OS that has many advantages and lots of features to make it easier for us to do various jobs, one of which is selling tickets using android for ticket sales so that ticket sales work more efficiently. today's smartphone is not only a means of communication, but smart phones have many uses, including for business, games, payments, etc. With the development of science and technology, people's lifestyles have been like culture, economy, society, and education, So this research we use android to be able to run the e-ticket application using a Bluetooth printer to make it more efficient place and time for data management which later this application is made with a hybrid mobile application with fremwork7 to connect to our database using API and MySQL.